All I want is everything : a Gossip Girl novel - Von Ziegesar, Cecily (Little, Brown, 2003)
Chronicles the activities of two friends, Serena and Blair, and a group of wealthy students from exclusive private schools in Manhattan during Christmas break of their senior year.